2016
DOI: 10.1126/sciadv.1500980
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of human dopamine β-hydroxylase at 2.9 Å resolution

Abstract: This first structure of the enzyme converting dopamine to norepinephrine provides new perspectives on numerous disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 68 publications
(100 reference statements)
4
120
0
2
Order By: Relevance
“…For many years, PHM was the only one of these three enzymes that had been crystallographically characterized. Recently, the first crystal structure of DβM was published [59]. Two different conformations of the enzyme were observed; one conformation, similar to PHM and called the open conformation, showed the two copper binding sites ~14 Å apart, while the other, called the closed conformation, showed the binding sites ~4 to 5 Å apart.…”
Section: Single Copper Active Sitesmentioning
confidence: 99%
“…For many years, PHM was the only one of these three enzymes that had been crystallographically characterized. Recently, the first crystal structure of DβM was published [59]. Two different conformations of the enzyme were observed; one conformation, similar to PHM and called the open conformation, showed the two copper binding sites ~14 Å apart, while the other, called the closed conformation, showed the binding sites ~4 to 5 Å apart.…”
Section: Single Copper Active Sitesmentioning
confidence: 99%
“…The lack of magnetic coupling between these sites distinguishes this class as "noncoupled" binuclear copper monooxygenases, in contrast to coupled binuclear copper enzymes (tyrosinase, hemocyanin, etc.). Intriguingly, a recent structure of dimeric DβM (7) shows an "open" conformation reminiscent of PHM in one apo monomer (predicted Cu-Cu distance ∼14 Å) and a "closed" conformation in the second half-apo monomer with a significantly contracted core (predicted Cu-Cu distance ∼5 Å). This suggests that the domains containing Cu H and Cu M have some conformational flexibility; however, it is currently unknown whether this is relevant to turnover.…”
mentioning
confidence: 99%
“…A recent study reported the DBH crystal structure, revealing four domains (the DOMON (dopamine b-monooxygenase N-terminal) domain, which forms a possible metal-binding site and a ligandbinding pocket; the catalytic CuH and CuM domains; and the C-terminal dimerization domain), providing new molecular insights into the catalytic mechanism, as well as the destructive disorders of both physiological and neurological origin of the DBH enzyme and the DA system [60]. On the other hand, the enzymatic activity and plasma level of DBH show wide interindividual variation modulated by genetic inheritance [27].…”
Section: Discussionmentioning
confidence: 99%